Muatan Dakwah Dalam Tradisi Sungkemen Sebagai Kearifan Lokal di Desa Tanah Merah, Kecamatan Perbaungan, Kabupaten Serdang Bedagai - Sabila, Rizka Ayu; Tanjung, Muaz (Jayapangus Press, 2025)
Culture and religion are two directions that are very close to the lives of Indonesian people. One culture that is close to the value of hospitality and full of moral values ​​in Indonesia is sungkeman. The purpose of this writing is to find out the content of da'wah in the sungkeman tradition. This is expected to help and increase the reader's insight into it. This research was conducted in Tanah Merah Village, Perbaungan District, Serdang Bedagai Regency using qualitative research methods. This approach uses methods such as interviews, participatory observation, literature studies, audio or video analysis and documentation to collect diverse and in-depth data. The stages of this research are data collection where researchers look for references to local traditional figures and are based on books, articles, data reduction, data presentation, and conclusions. This research was conducted by interviewing 2 informants online, namely Traditional Figures and Religious Figures in Tanah Merah Village. Based on the results of the study, it can be concluded that the sungkeman tradition is not prohibited and does not conflict with Islamic law. This tradition is considered very sacred and meaningful, where there are many Preaching Contents contained in the Sungkeman tradition including Family Values, Silaturahmi Values, Humility Values, Forms of Gratitude and Gratitude, as well as Self-Awareness Rituals.